Antibacterial and deodorizing moisture-absorbing pellets for fecal diversion ostomy bags and preparation method thereof
By integrating a multifunctional mesoporous silica-supported silver-zinc oxide composite antibacterial agent and a rare earth-doped zinc oxide/montmorillonite composite photocatalytic deodorant, the problems of odor and microbial growth in ostomy bags are solved, achieving long-lasting nursing effects and improving patients' quality of life.
Patent Information
- Application Number
- CN202610332652.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-18
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-03-18
AI Technical Summary
Existing ostomy bag care products have the problem of short-term and incomplete effects in deodorization and antibacterial properties, and cannot effectively solve the problems of foul odor and microbial growth in the ostomy bag, leading to a decline in the patient's quality of life.
A multifunctional integrated antibacterial, deodorizing, and moisture-absorbing pellet was prepared by using mesoporous silica-supported silver-zinc oxide composite antibacterial agent and rare earth-doped zinc oxide/montmorillonite composite photocatalytic deodorizer, combined with anhydrous calcium chloride and activated carbon, through ball milling, drying, and spray molding.
It achieves a synergistic effect of long-lasting antibacterial, deodorizing, moisture-absorbing and lubricating functions, maintaining a clean, dry and low-bacterial environment inside the ostomy bag, improving patient comfort and quality of life.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of medical device and medical material technology, specifically relating to an antibacterial, deodorizing, and moisture-absorbing pellet for fecal diversion ostomy bags and its preparation method. Background Technology
[0002] Enterostomy, a crucial surgical treatment for severe intestinal diseases and a life-saving procedure, has been widely adopted. However, this surgery alters the patient's normal excretion pathway, requiring the creation of an artificial opening (ostomy) in the abdominal wall to guide the intestines out. Post-surgery, patients must rely on an external ostomy bag for life to collect waste. This presents patients with long-term and severe challenges, both physiologically and psychologically. Physiologically, the retention of waste (especially feces) in the ostomy bag creates severe odor problems. These odors primarily originate from small-molecule volatile malodorous substances such as ammonia, hydrogen sulfide, indole, and skatole, produced by the decomposition of sulfur- and nitrogen-containing organic matter by microorganisms in the sealed environment of the bag. These odors easily escape, causing discomfort and embarrassment not only to the patient but also devastatingly impacting their social activities, mental health, and even social image, leading to feelings of inferiority, anxiety, and depression, and severely reducing their quality of life. Meanwhile, the warm, moist, and organic-rich environment inside the ostomy bag becomes a breeding ground for bacteria and other microorganisms to grow and multiply rapidly, greatly increasing the risk of contact dermatitis, infection, or even ulceration around the stoma, and bringing continuous pain and nursing burden to patients.
[0003] To address the aforementioned issues, current nursing products on the market primarily focus on deodorization, but their design concepts and functional performance have significant limitations. The most common is activated charcoal deodorizing tablets based on the principle of physical adsorption. These products utilize the porous structure of activated charcoal to adsorb odor molecules. However, their adsorption capacity is limited, and they easily become saturated and ineffective in humid environments and environments with high organic concentrations, requiring frequent replacement. Furthermore, their adsorption capacity for highly polar odor molecules such as ammonia is weak. More importantly, simple physical adsorption cannot solve the fundamental problem of microbial growth and lacks antibacterial function. Another type of product is spray-on deodorizing lubricants, which typically mix deodorizing ingredients with lubricants and form a coating inside the ostomy bag through spraying. While these products also have some lubricating function, their effective dosage is low, the area of action is limited, and the duration of effect is very short, requiring frequent application by patients. Long-term use is costly, and the organic solvents or fragrance components in some sprays may irritate the already damaged or sensitive skin around the stoma.
[0004] In summary, existing technologies primarily address single issues (such as deodorization or lubrication alone), offering only short-lived and incomplete results. There is a lack of innovative nursing solutions that can synergistically, effectively, and comprehensively address the complex and harsh environment inside ostomy bags. Clinically, there is an urgent need for a patient care material that integrates multiple functions, including highly effective antibacterial properties, long-lasting deodorization, rapid moisture absorption, and necessary lubrication. This material must be able to adapt to the dark, moist, and bacteria-rich environment inside ostomy bags, providing long-lasting effects and ease of use, thereby fundamentally improving the living conditions of ostomy patients. This represents a clear and pressing technological gap in the current field of ostomy care, and is also an inevitable direction for industrial upgrading and meeting patients' demands for a higher quality of life. Summary of the Invention
[0005] In view of the shortcomings of the prior art, the purpose of this invention is to provide an antibacterial, deodorizing, and moisture-absorbing pellet for fecal ostomy bag and its preparation method.
[0006] In a first aspect, the present invention provides a method for preparing antibacterial, deodorizing, and moisture-absorbing pellets for fecal ostomy bags, comprising the following steps: S1. By weight, 15-25 parts of mesoporous silica-supported silver-zinc oxide composite antibacterial agent, 20-30 parts of rare earth-doped zinc oxide / montmorillonite composite photocatalytic deodorizer, 10-15 parts of rosin powder, 8-12 parts of magnesium stearate, 25-35 parts of activated carbon powder, and 10-15 parts of anhydrous calcium chloride powder are placed in the ball mill jar of a ball mill. Anhydrous ethanol is added, and argon gas is introduced. The mixture is ball-milled to obtain a ball mill slurry. The ball mill slurry is then transferred to a vacuum drying oven at 38-42℃ and dried to obtain a functional masterbatch. The functional masterbatch is transferred to a stirred pellet mill, and an anhydrous ethanol solution containing 8-12 parts of polyethylene glycol 6000 is added through a spray device under continuous stirring to obtain wet pellets. S2. Place the wet pellets into a drying oven and dry them first at 48-52℃, then at 88-92℃, and then at 98-102℃. After drying, cool them to 38-42℃ and age them.
[0007] In this invention, the preparation of the antibacterial, deodorizing, and moisture-absorbing pellets for ostomy bags integrates the principles of physical composite and functional integration. Multiple functional powders are uniformly dispersed at the nanoscale through wet ball milling in an inert atmosphere, and then vacuum dried to obtain a functional masterbatch with good flowability. Using a pharmaceutical polymer solution as a binding medium, the polymer chains entwine the particles of each component during atomization. After ethanol evaporation, a continuous network structure is formed, firmly integrating the moisture-absorbing components, antibacterial units, and deodorizing materials into a dense pellet. Gradient drying and slow cooling aging processes eliminate internal stress and optimize the pore structure. In the final product, calcium chloride and activated carbon synergistically construct gradient moisture-absorbing channels to quickly lock in moisture; rosin and magnesium stearate regulate surface hydrophobicity and mechanical strength; the composite antibacterial agent inhibits pathogenic microorganisms through a dual pathway of ion slow release and photocatalysis; and the composite deodorizing agent continuously decomposes odor molecules under light. The components are spatially uniform, their functions do not interfere with each other, and they synergistically enhance each other, jointly maintaining a dry, clean, and hygienic microenvironment within the ostomy bag, significantly improving patient comfort and quality of life.
[0008] According to a preferred embodiment of the present invention, in step S1, the ball milling mixing time is 1.5-2 hours.
[0009] According to a preferred embodiment of the present invention, in step S2, the drying time at 48-52°C is 1-2 hours.
[0010] According to a preferred embodiment of the present invention, the preparation method of the mesoporous silica-supported silver-zinc oxide composite antibacterial agent includes: A1, dissolving 0.4-0.6 parts by weight of hexadecyltrimethylammonium bromide in a mixture of 40-60 parts deionized water and 3-5 parts ammonia water, stirring, adding 1-1.5 parts of tetraethyl orthosilicate, reacting at 38-42°C to obtain a mixture; centrifuging the mixture to obtain a precipitate, washing the precipitate with deionized water until neutral, then replacing it with anhydrous ethanol, and then dispersing it in anhydrous ethanol to obtain a suspension; and then... 0.03-0.05 parts silver nitrate and 0.15-0.25 parts zinc nitrate are dissolved in anhydrous ethanol, and 0.02-0.05 parts mercaptopropyltrimethoxysilane are added to obtain a mixed solution; the mixed solution is added to the suspension and stirred at 58-62℃ to obtain a reaction mixture; A2, the reaction mixture is centrifuged to obtain a solid product, the solid product is washed with ethanol and then heated to 395-405℃ in a tube furnace and calcined in a nitrogen / hydrogen atmosphere; after calcination, the furnace is cooled to room temperature under continuous nitrogen / hydrogen atmosphere and then ground.
[0011] In this invention, the construction of the mesoporous silica-supported silver-zinc oxide composite antibacterial agent relies on a template-guided and interfacial chemical synergistic mechanism. First, a cationic surfactant self-assembles in an alkaline aqueous phase to form ordered micelles, where silicon source molecules hydrolyze and condense on their surface, constructing a silica framework with high specific surface area and regular channels. After washing and displacement, a metal salt and mercaptosilane coupling agent are introduced in an anhydrous ethanol environment: the mercapto groups anchor silver and zinc ions through strong coordination, while the silane end groups condense with the hydroxyl groups on the silica pore walls, achieving precise positioning and uniform distribution of the metal precursor within the channels. Subsequently, heat treatment in a reducing atmosphere selectively reduces silver ions to zero-valent nanoparticles, and the zinc component is converted into semiconductor oxide nanocrystals, both coexisting within the mesoporous confined space. This structure avoids the aggregation and deactivation of active components while forming a silver-zinc oxide heterojunction, significantly enhancing the photogenerated carrier separation efficiency and reactive oxygen species generation capacity, endowing the material with broad-spectrum, long-lasting, and slow-release synergistic antibacterial function.
[0012] According to a preferred embodiment of the present invention, in step A1, the reaction time at 38-42°C is 2-4 hours.
[0013] According to a preferred embodiment of the present invention, in step A2, the calcination time in a nitrogen / hydrogen atmosphere is 3-6 hours.
[0014] According to a preferred embodiment of the present invention, the preparation method of the rare earth-doped zinc oxide / montmorillonite composite photocatalytic deodorizer includes: B1, dissolving 0.5-0.7 parts by weight of zinc nitrate, 0.01-0.03 parts by weight of cerium nitrate and 0.005-0.015 parts by weight of lanthanum nitrate in deionized water to obtain solution A; dispersing 0.3-0.5 parts by weight of sodium-based montmorillonite in deionized water to obtain suspension B; adding solution A dropwise to suspension B while stirring, and simultaneously adding an aqueous solution containing 0.8-1.2 parts by weight of urea, adjusting the pH to 8.5-9.5, and reacting in a water bath at 84-86°C to obtain a mixture; B2, centrifuging the mixture to obtain a solid product, washing the solid product, and drying it at 78-82°C to obtain a dried powder; calcining the dried powder at 445-455°C in an air atmosphere.
[0015] In this invention, the preparation of the rare-earth-doped zinc oxide / montmorillonite composite photocatalytic deodorizer originates from the coupling effect of homogeneous urea precipitation and lattice doping. Montmorillonite is fully dispersed in the aqueous phase, providing a layered adsorption substrate. After the metal salt solution and urea are introduced simultaneously, the urea undergoes slow hydrolysis upon heating, resulting in a stable increase in the pH of the system. This promotes the uniform nucleation and deposition of zinc, cerium, and lanthanum hydroxide precursors on the outer surface and edge regions of the montmorillonite, effectively inhibiting particle agglomeration. Upon heat treatment, the precursors are converted into oxides, and rare-earth ions, due to ionic radius matching, embed into the zinc oxide lattice, inducing lattice distortion and oxygen vacancy generation, broadening the photoresponse range and improving carrier lifetime. The high adsorption capacity of montmorillonite enriches odor molecules near the catalytically active sites, while rare-earth-doped zinc oxide generates reactive oxygen species under visible light excitation, efficiently mineralizing odor-causing substances such as hydrogen sulfide and ammonia. The two work synergistically to achieve an "adsorption-catalysis-regeneration" cycle, ensuring long-term stability of the deodorization performance.
[0016] According to a preferred embodiment of the present invention, in step B1, the reaction time in a water bath at 84-86°C is 5-10 hours.
[0017] According to a preferred embodiment of the present invention, in step B2, the calcination time at 445-455°C is 2-4 hours.
[0018] A second aspect of the present invention provides an antibacterial, deodorizing, and moisture-absorbing pellet for a fecal diversion ostomy bag, prepared according to the method described above.
[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) The most outstanding technical effect of this invention is that it successfully achieves the integrated and long-lasting synergistic effect of the four core functions of antibacterial, deodorizing, moisture absorption and lubrication. Specifically, the mesoporous silica-loaded silver-zinc oxide composite antibacterial agent and the rare earth-doped zinc oxide / montmorillonite composite photocatalytic deodorizer in the pills constitute a dual-core active system. The former provides a broad-spectrum and long-lasting antibacterial ability through the synergy of silver and zinc oxide, which can effectively inhibit the growth of various pathogenic bacteria such as Escherichia coli and Staphylococcus aureus in the ostomy bag, thereby reducing the risk of infection and inflammation from the source; the latter not only uses the adsorption characteristics of montmorillonite and activated carbon to quickly capture odor molecules, but also endows zinc oxide with photocatalytic activity under visible light and even weak light conditions through rare earth element doping, which can efficiently decompose the adsorbed ammonia, hydrogen sulfide and other malodorous organic matter into harmless substances, realizing the qualitative change from "physical adsorption masking" to "chemical catalytic elimination", and the deodorization is more thorough and lasting. Meanwhile, the combination of anhydrous calcium chloride and activated carbon produces a synergistic effect of physical adsorption and chemical hygroscopicity, rapidly and significantly absorbing moisture from excrement, keeping the ostomy bag dry. This improves patient comfort and disrupts the moist environment conducive to microbial growth. The addition of magnesium stearate provides self-lubrication during the slow action of the pill, reducing excrement adhesion and friction against the bag. These four functions are not simply superimposed, but rather, through the overall design of the pill, they are released in an orderly and demanding manner in a moist environment, mutually reinforcing each other to jointly create a long-lasting, clean, dry, low-bacterial, and odorless microenvironment within the ostomy bag.
[0020] (2) The key effect of this invention stems from the performance leap brought about by the original design of the microstructure of the two core functional materials. For the antibacterial agent, mesoporous silica is used as a carrier. Its regular and orderly nanopores not only greatly increase the loading area of the active components of silver and zinc oxide, but also effectively prevent the migration and aggregation of nano-metal particles through the nano-confinement effect, ensuring the activity stability during long-term storage and use. More ingeniously, this structure realizes the intelligent slow release of antibacterial ions. That is, in a humid environment, the active components can be released slowly and in a controlled manner from the pores, avoiding the problem of early high concentration irritating the skin and rapid failure in the later stage caused by the instantaneous release of traditional antibacterial agents, thereby extending the effective antibacterial period by several times. For deodorants, rare earth elements such as cerium and lanthanum are introduced to co-dopate zinc oxide. This design introduces new energy levels into the band structure of zinc oxide, significantly broadening its response range to the visible light spectrum. This allows the material to be activated even under extremely low light conditions inside the ostomy bag, generating highly oxidizing photogenerated holes and free radicals, thus solving the industry problem of traditional photocatalysts (such as titanium dioxide) completely failing in the absence of light or in dark environments. Simultaneously, the montmorillonite sheet support not only disperses and stabilizes the nano-zinc oxide, but its strong ion exchange and adsorption capabilities also pre-enrich the target odor molecules, greatly improving the local concentration and degradation efficiency of the photocatalytic reaction. The synergy of these two materials enables the pellets to exhibit stability and efficiency unmatched by ordinary mixtures when facing complex real-world application environments.
[0021] (3) This invention has achieved excellent practical results in terms of preparation process and final product form. All raw materials used in the entire preparation process are commercially available chemically pure or pharmaceutical grade products, without the need for customized special chemicals. Moreover, the synthesis and molding steps all use conventional equipment in the chemical and pharmaceutical fields, with clear conditions and parameters, good reproducibility, and a solid foundation for large-scale production. Through precise process control, the final pills have the characteristics of uniform size, suitable mechanical strength, and controllable disintegration rate in a humid environment. Compared with liquid spray, this solid pill form has significant advantages such as precise dosage, long duration of action, no need for frequent operation, convenient storage and carrying, and less susceptibility to contamination or leakage. Patients only need to put a few pills into the ostomy bag to continuously exert comprehensive nursing effects for up to tens of hours, greatly improving the convenience and compliance of use, and reducing the overall cost of long-term care. In summary, driven by material science innovation, this invention has successfully developed a new type of ostomy care product that is multifunctional, has excellent long-lasting performance, is easy to use, and is easy to industrialize, providing a practical and effective technical solution for solving the physical and mental suffering of ostomy patients and improving their quality of life. Detailed Implementation
[0022] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.
[0023] Example 1 This embodiment provides a method for preparing antibacterial, deodorizing, and moisture-absorbing pellets for fecal ostomy bags, the steps of which include: First, a mesoporous silica-supported silver-zinc oxide composite antibacterial agent was prepared. 0.5 g of hexadecyltrimethylammonium bromide was dissolved in a mixture of 50 mL of deionized water and 4 mL of 28% ammonia solution. The mixture was stirred at 600 rpm, and 1.2 g of tetraethyl orthosilicate was added at a rate of 1.5 mL / min. The reaction was carried out at 40 °C for 3 h to obtain a mixture. The mixture was centrifuged to obtain a precipitate, which was washed with deionized water until neutral, then washed three times with anhydrous ethanol. The precipitate was then dispersed in 50 mL of anhydrous ethanol to obtain a suspension. 0.04 g of silver nitrate and 0.2 g of zinc nitrate were dissolved in 20 mL of anhydrous ethanol, and 0.03 g of mercaptopropyltrimethoxysilane was added to obtain a mixed solution. This mixed solution was added to the aforementioned suspension, and the mixture was stirred at 60 °C for 6 h to obtain a reaction mixture. The reaction mixture was centrifuged to obtain a solid product. This solid product was washed with ethanol and then placed in a tube furnace and heated to 400°C at a heating rate of 2°C / min. It was then calcined for 4 hours in a nitrogen-hydrogen mixture with a volume ratio of 95:5. After calcination, the mixture was cooled to room temperature in the furnace under the same protective atmosphere. The mixture was then ground to obtain a powdered mesoporous silica-supported silver-zinc oxide composite antibacterial agent.
[0024] Next, a rare-earth-doped zinc oxide / montmorillonite composite photocatalytic deodorizer was prepared. 0.6 g of zinc nitrate, 0.02 g of cerium nitrate, and 0.01 g of lanthanum nitrate were dissolved in 50 mL of deionized water to obtain solution A. 0.4 g of sodium-based montmorillonite was dispersed in 100 mL of deionized water to obtain suspension B. Under stirring, solution A was added dropwise to suspension B at a rate of 2 mL / min, while simultaneously adding 50 mL of an aqueous solution containing 1.0 g of urea. The dropping rate was controlled to raise the pH of the reaction system and eventually stabilize it at 9.0. The reaction was carried out in a water bath at 85 °C for 7 h to obtain a mixture. This mixture was centrifuged to obtain a solid product. The solid product was washed with deionized water until no nitrate ions were detected in the filtrate, and then dried at 80 °C for 12 h to obtain a dried powder. The powder was heated to 450°C for 3 hours in air at a heating rate of 3°C / min, and then naturally cooled to room temperature to obtain a rare earth-doped zinc oxide / montmorillonite composite photocatalytic deodorizer.
[0025] Finally, antibacterial, deodorizing, and moisture-absorbing pellets for fecal ostomy bags were prepared. 20g of the antibacterial agent, 25g of the deodorizing agent, 12g of rosin powder, 10g of magnesium stearate, 30g of activated carbon powder, and 12g of anhydrous calcium chloride powder were placed in the grinding jar of a planetary ball mill. 50mL of anhydrous ethanol was added as the liquid medium, and argon gas was introduced to replace the air. The ball-to-material mass ratio was set to 3:1, and the mixture was ball-milled at 300rpm for 1.8h to obtain a ball-milled slurry. This slurry was then transferred to a 40℃ vacuum drying oven and dried to constant weight to obtain a dried functional masterbatch. The functional masterbatch was transferred to a stirred pelletizing machine, and under continuous stirring, a 50mL anhydrous ethanol solution containing 10g of polyethylene glycol 6000 was atomized through a spray device as a binder. The spray rate was controlled to allow the material to gradually agglomerate, resulting in wet pellets with a particle size of 10mm. The wet pellets were placed in a hot air circulating drying oven with an air velocity of 0.8 m / s. They were first dried at 50°C for 1.5 hours for shaping, then at 90°C for 3 hours to remove solvent, and finally at 100°C for 0.5 hours to enhance strength. After drying, the heat source was turned off, and the pellets were slowly cooled to below 40°C at a rate of 10°C / hour within the drying oven. They were then transferred to an environment with a temperature of 22°C and a relative humidity of 45% for aging for 3 hours. After removing defective pellets, the finished product, antibacterial, deodorizing, and moisture-absorbing pellets for fecal ostomy bags, was obtained.
[0026] Example 2 The difference between this embodiment and Example 1 is that, firstly, a mesoporous silica-supported silver-zinc oxide composite antibacterial agent is prepared. 0.5 g of hexadecyltrimethylammonium bromide was dissolved in a mixture of 50 mL of deionized water and 4 mL of 28% ammonia solution. The mixture was stirred at 600 rpm, and 1.2 g of tetraethyl orthosilicate was added at a rate of 1.5 mL / min. The reaction was carried out at 40°C for 3 h to obtain a mixture. The mixture was centrifuged to obtain a precipitate, which was washed with deionized water until neutral, then washed three times with anhydrous ethanol. The precipitate was then dispersed in 50 mL of anhydrous ethanol to obtain a suspension. 0.04 g of silver nitrate and 0.2 g of zinc nitrate were dissolved in 20 mL of anhydrous ethanol, and 0.03 g of mercaptopropyltrimethoxysilane was added to obtain a mixed solution. This mixed solution was added to the aforementioned suspension, and the mixture was stirred at 60°C for 6 h to obtain a reaction mixture. The reaction mixture was centrifuged to obtain a solid product. This solid product was washed with ethanol and then placed in a tube furnace and heated to 400°C at a heating rate of 2°C / min. It was then calcined for 4 hours in a nitrogen-hydrogen mixture with a volume ratio of 95:5. After calcination, the mixture was cooled to room temperature in the furnace under the same protective atmosphere. The mixture was then ground to obtain a powdered mesoporous silica-supported silver-zinc oxide composite antibacterial agent.
[0027] Next, a rare-earth-doped zinc oxide / montmorillonite composite photocatalytic deodorizer was prepared. 0.6 g of zinc nitrate, 0.02 g of cerium nitrate, and 0.01 g of lanthanum nitrate were dissolved in 50 mL of deionized water to obtain solution A. 0.4 g of sodium-based montmorillonite was dispersed in 100 mL of deionized water to obtain suspension B. Under stirring, solution A was added dropwise to suspension B at a rate of 2 mL / min, while simultaneously adding 50 mL of an aqueous solution containing 1.0 g of urea. The dropping rate was controlled to raise the pH of the reaction system and eventually stabilize it at 9.0. The reaction was carried out in a water bath at 85 °C for 7 h to obtain a mixture. This mixture was centrifuged to obtain a solid product. The solid product was washed with deionized water until no nitrate ions were detected in the filtrate, and then dried at 80 °C for 12 h to obtain a dried powder. The powder was heated to 450°C for 3 hours in air at a heating rate of 3°C / min, and then naturally cooled to room temperature to obtain a rare earth-doped zinc oxide / montmorillonite composite photocatalytic deodorizer.
[0028] Finally, antibacterial, deodorizing, and moisture-absorbing pellets for fecal ostomy bags were prepared. 25g of the antibacterial agent, 20g of the deodorizing agent, 10g of rosin powder, 12g of magnesium stearate, 35g of activated carbon powder, and 10g of anhydrous calcium chloride powder were placed in the grinding jar of a planetary ball mill. 55mL of anhydrous ethanol was added as the liquid medium, and argon gas was introduced to replace the air. The ball-to-material mass ratio was set to 3:1, and the mixture was ball-milled at 250rpm for 2.0h to obtain a ball-milled slurry. This slurry was then transferred to a 40℃ vacuum drying oven and dried to constant weight to obtain a dried functional masterbatch. The functional masterbatch was transferred to a stirred pelletizing machine, and under continuous stirring, 60mL of anhydrous ethanol solution containing 12g of polyethylene glycol 6000 was atomized through a spray device as a binder. The spray rate was controlled to allow the material to gradually agglomerate, resulting in wet pellets with a particle size of 10mm. The wet pellets were placed in a hot air circulating drying oven with an air velocity of 0.8 m / s. They were first dried at 52℃ for 1.0 h for shaping, then at 92℃ for 2.0 h to remove solvent, and finally at 102℃ for 0.5 h to enhance strength. After drying, the heat source was turned off, and the pellets were slowly cooled to below 40℃ at a rate of 10℃ / h within the drying oven. They were then transferred to an environment with a temperature of 25℃ and a relative humidity of 50% for aging for 4 h. After removing defective pellets, the antibacterial, deodorizing, and moisture-absorbing pellets for fecal ostomy bags were obtained.
[0029] Example 3 The difference between this embodiment and Example 1 is that, firstly, a mesoporous silica-supported silver-zinc oxide composite antibacterial agent is prepared. 0.5 g of hexadecyltrimethylammonium bromide was dissolved in a mixture of 50 mL of deionized water and 4 mL of 28% ammonia solution. The mixture was stirred at 600 rpm, and 1.2 g of tetraethyl orthosilicate was added at a rate of 1.5 mL / min. The reaction was carried out at 40°C for 3 h to obtain a mixture. The mixture was centrifuged to obtain a precipitate, which was washed with deionized water until neutral, then washed three times with anhydrous ethanol. The precipitate was then dispersed in 50 mL of anhydrous ethanol to obtain a suspension. 0.04 g of silver nitrate and 0.2 g of zinc nitrate were dissolved in 20 mL of anhydrous ethanol, and 0.03 g of mercaptopropyltrimethoxysilane was added to obtain a mixed solution. This mixed solution was added to the aforementioned suspension, and the mixture was stirred at 60°C for 6 h to obtain a reaction mixture. The reaction mixture was centrifuged to obtain a solid product. This solid product was washed with ethanol and then placed in a tube furnace and heated to 400°C at a heating rate of 2°C / min. It was then calcined for 4 hours in a nitrogen-hydrogen mixture with a volume ratio of 95:5. After calcination, the mixture was cooled to room temperature in the furnace under the same protective atmosphere. The mixture was then ground to obtain a mesoporous silica-supported silver-zinc oxide composite antibacterial agent.
[0030] Next, a rare-earth-doped zinc oxide / montmorillonite composite photocatalytic deodorizer was prepared. 0.6 g of zinc nitrate, 0.02 g of cerium nitrate, and 0.01 g of lanthanum nitrate were dissolved in 50 mL of deionized water to obtain solution A. 0.4 g of sodium-based montmorillonite was dispersed in 100 mL of deionized water to obtain suspension B. Under stirring, solution A was added dropwise to suspension B at a rate of 2 mL / min, while simultaneously adding 50 mL of an aqueous solution containing 1.0 g of urea. The dropping rate was controlled to raise the pH of the reaction system and eventually stabilize it at 9.0. The reaction was carried out in a water bath at 85 °C for 7 h to obtain a mixture. This mixture was centrifuged to obtain a solid product. The solid product was washed with deionized water until no nitrate ions were detected in the filtrate, and then dried at 80 °C for 12 h to obtain a dried powder. The powder was heated to 450°C for 3 hours in air at a heating rate of 3°C / min, and then naturally cooled to room temperature to obtain a rare earth-doped zinc oxide / montmorillonite composite photocatalytic deodorizer.
[0031] Finally, antibacterial, deodorizing, and moisture-absorbing pellets for fecal ostomy bags were prepared. 15g of the antibacterial agent, 30g of the deodorizing agent, 15g of rosin powder, 8g of magnesium stearate, 25g of activated carbon powder, and 15g of anhydrous calcium chloride powder were placed in the grinding jar of a planetary ball mill. 45mL of anhydrous ethanol was added as the liquid medium, and argon gas was introduced to replace the air. The ball-to-material mass ratio was set to 3:1, and the mixture was ball-milled at 350rpm for 1.5 hours to obtain a ball-milled slurry. This slurry was then transferred to a 40℃ vacuum drying oven and dried to constant weight to obtain a dried functional masterbatch. The functional masterbatch was transferred to a stirred pelletizing machine, and under continuous stirring, a 40mL anhydrous ethanol solution containing 8g of polyethylene glycol 6000 was atomized through a spray device as a binder. The spray rate was controlled to allow the material to gradually agglomerate, resulting in wet pellets with a particle size of 10mm. The wet pellets were placed in a hot air circulating drying oven with an air velocity of 0.8 m / s. They were first dried at 48°C for 2.0 h for shaping, then at 88°C for 4.0 h to remove solvent, and finally at 98°C for 1.0 h to enhance strength. After drying, the heat source was turned off, and the pellets were slowly cooled to below 40°C at a rate of 10°C / h within the drying oven. They were then transferred to an environment with a temperature of 20°C and a relative humidity of 40% for aging for 2 h. After removing defective pellets, the antibacterial, deodorizing, and moisture-absorbing pellets for fecal ostomy bags were obtained.
[0032] Comparative Example 1 The difference between this comparative example and Example 1 is that this comparative example does not use the mesoporous silica-supported silver-zinc oxide composite antibacterial agent and the rare earth-doped zinc oxide / montmorillonite composite photocatalytic deodorizer. In preparing the antibacterial, deodorizing, and moisture-absorbing pellets for fecal ostomy bags, 20g of micron-sized zinc oxide powder was used instead of the mesoporous silica-supported silver-zinc oxide composite antibacterial agent, and 25g of micron-sized titanium dioxide powder was used instead of the rare earth-doped zinc oxide / montmorillonite composite photocatalytic deodorizer. The remaining components and amounts were 12g of rosin powder, 10g of magnesium stearate, 30g of activated carbon powder, and 12g of anhydrous calcium chloride powder. All the above powders were placed in the ball mill jar of a planetary ball mill, 50mL of anhydrous ethanol was added as the liquid medium, argon gas was introduced to replace the air, the ball-to-powder mass ratio was set to 3:1, and the mixture was ball-milled at 300rpm for 1.8h to obtain a ball-milled slurry. This slurry was then transferred to a 40℃ vacuum drying oven and dried to constant weight to obtain a dried functional masterbatch. The functional masterbatch was transferred to a mixing pelletizing machine. Under continuous stirring, a 50mL anhydrous ethanol solution containing 10g of polyethylene glycol 6000 was atomized through a spray device as a binder. The spray rate was controlled to gradually agglomerate the material, resulting in wet pellets with a particle size of 10mm. The wet pellets were then sent to a hot air circulating drying oven with an air velocity of 0.8m / s. They were first dried at 50℃ for 1.5h for shaping, then at 90℃ for 3h to remove the solvent, and finally at 100℃ for 0.5h to enhance strength. After drying, the heat source was turned off, and the pellets were cooled to below 40℃ at a rate of 10℃ / h in the drying oven. They were then transferred to an environment with a temperature of 22℃ and a relative humidity of 45% for 3h for aging. After removing defective pellets, the control pellets were obtained.
[0033] Comparative Example 2 The difference between this comparative example and Example 1 is that, firstly, a rare earth-doped zinc oxide / montmorillonite composite photocatalytic deodorizer was prepared. 0.6 g of zinc nitrate, 0.02 g of cerium nitrate, and 0.01 g of lanthanum nitrate were dissolved together in 50 mL of deionized water to obtain solution A. 0.4 g of sodium-based montmorillonite was dispersed in 100 mL of deionized water to obtain suspension B. Under stirring, solution A was added dropwise to suspension B at a rate of 2 mL / min, while simultaneously adding 50 mL of an aqueous solution containing 1.0 g of urea. The dropping rate was controlled to raise the pH of the reaction system and eventually stabilize it at 9.0. The reaction was carried out in a water bath at 85°C for 7 h to obtain a mixture. This mixture was centrifuged to obtain a solid product. The solid product was washed with deionized water until no nitrate ions were detected in the filtrate, and then dried at 80°C for 12 h to obtain a dried powder. The powder was heated to 450°C for 3 hours in air at a heating rate of 3°C / min, and then naturally cooled to room temperature to obtain a rare earth-doped zinc oxide / montmorillonite composite photocatalytic deodorizer.
[0034] In preparing the pellets, 20g of micron-sized zinc oxide powder was used to replace the mesoporous silica-supported silver-zinc oxide composite antibacterial agent. 25g of the deodorant prepared above was used, and the remaining components and their amounts were 12g of rosin powder, 10g of magnesium stearate, 30g of activated carbon powder, and 12g of anhydrous calcium chloride powder. All the powders were placed in the grinding jar of a planetary ball mill, and 50mL of anhydrous ethanol was added as the liquid medium. Argon gas was introduced to replace the air, and the ball-to-material mass ratio was set to 3:1. The mixture was ball-milled at 300rpm for 1.8h to obtain a ball-milled slurry. This slurry was then transferred to a 40℃ vacuum drying oven and dried to constant weight to obtain a dried functional masterbatch. The functional masterbatch was transferred to a stirred pellet mill, and under continuous stirring, a 50mL anhydrous ethanol solution containing 10g of polyethylene glycol 6000 was atomized through a spray device as a binder. The spray rate was controlled to allow the material to gradually agglomerate, resulting in wet pellets with a particle size of 10mm. The wet pellets were placed in a hot air circulating drying oven with an air velocity of 0.8 m / s. They were first dried at 50°C for 1.5 hours for shaping, then at 90°C for 3 hours to remove the solvent, and finally at 100°C for 0.5 hours to enhance strength. After drying, the heat source was turned off, and the pellets were cooled to below 40°C at a rate of 10°C / hour within the drying oven. They were then transferred to an environment with a temperature of 22°C and a relative humidity of 45% for 3 hours of aging. Defective pellets were removed to obtain the control pellets.
[0035] Comparative Example 3 The difference between this comparative example and Example 1 is that, firstly, a mesoporous silica-supported silver-zinc oxide composite antibacterial agent was prepared. 0.5 g of hexadecyltrimethylammonium bromide was dissolved in a mixture of 50 mL of deionized water and 4 mL of 28% ammonia solution. The mixture was stirred at 600 rpm, and 1.2 g of tetraethyl orthosilicate was added at a rate of 1.5 mL / min. The reaction was carried out at 40 °C for 3 h to obtain a mixture. The mixture was centrifuged to obtain a precipitate, which was washed with deionized water until neutral, then washed three times with anhydrous ethanol. The precipitate was then dispersed in 50 mL of anhydrous ethanol to obtain a suspension. 0.04 g of silver nitrate and 0.2 g of zinc nitrate were dissolved in 20 mL of anhydrous ethanol, and 0.03 g of mercaptopropyltrimethoxysilane was added to obtain a mixed solution. This mixed solution was added to the aforementioned suspension, and the mixture was stirred at 60 °C for 6 h to obtain a reaction mixture. The reaction mixture was centrifuged to obtain a solid product. This solid product was washed with ethanol and then placed in a tube furnace and heated to 400°C at a heating rate of 2°C / min. It was then calcined for 4 hours in a nitrogen-hydrogen mixture with a volume ratio of 95:5. After calcination, the mixture was cooled to room temperature in the furnace under the same protective atmosphere. The mixture was then ground to obtain a powdered mesoporous silica-supported silver-zinc oxide composite antibacterial agent.
[0036] In preparing the pellets, 20g of the antibacterial agent obtained above was used, and 25g of micron-sized titanium dioxide powder was used to replace the rare earth-doped zinc oxide / montmorillonite composite photocatalytic deodorizer. The remaining components and their amounts were 12g of rosin powder, 10g of magnesium stearate, 30g of activated carbon powder, and 12g of anhydrous calcium chloride powder. All the above powders were placed in the ball mill jar of a planetary ball mill, and 50mL of anhydrous ethanol was added as the liquid medium. Argon gas was introduced to replace the air, and the ball-to-material mass ratio was set to 3:1. The mixture was ball-milled at 300rpm for 1.8h to obtain a ball-milled slurry. This slurry was then transferred to a vacuum drying oven at 40℃ and dried to constant weight to obtain a dried functional masterbatch. The functional masterbatch was transferred to a stirred pellet mill, and under continuous stirring, a 50mL anhydrous ethanol solution containing 10g of polyethylene glycol 6000 was atomized through a spray device as a binder. The spray rate was controlled to allow the material to gradually agglomerate, resulting in wet pellets with a particle size of 10mm. The wet pellets were placed in a hot air circulating drying oven with an air velocity of 0.8 m / s. They were first dried at 50°C for 1.5 hours for shaping, then at 90°C for 3 hours to remove the solvent, and finally at 100°C for 0.5 hours to enhance strength. After drying, the heat source was turned off, and the pellets were slowly cooled to below 40°C at a rate of 10°C / hour within the drying oven. They were then transferred to an environment with a temperature of 22°C and a relative humidity of 45% for 3 hours of aging. Defective pellets were removed to obtain the control pellets.
[0037] According to relevant national and industry standards, the performance of the antibacterial, deodorizing, and moisture-absorbing pellets for fecal ostomy bags provided in the above embodiments and comparative examples was tested. The test methods are as follows: Antibacterial performance was evaluated using two tests: inhibition zone diameter and quantitative antibacterial rate. In the inhibition zone test, a single intact pill was placed in the center of a sterile nutrient agar plate, and 0.1 mL of a 1×10⁻⁶ concentration was precisely dotted onto its surface using a pipette. 6 The test bacterial suspension was prepared at CFU / mL, ensuring that the droplets covered the surface of the pills. The test bacterial species were *Escherichia coli* ATCC25922 and *Staphylococcus aureus* ATCC6538. The plates were incubated at 37°C for 24 hours. After incubation, the vertical distance from the edge of the pill to the edge of the inhibition zone was measured using a 0.1 mm vernier caliper; the average value was taken for each sample from two vertical directions.
[0038] The quantitative antibacterial rate test was performed in a sterile centrifuge tube. 5 mL of phosphate buffer and a single pill were added to the tube, followed by 0.1 mL of the bacterial suspension at the above concentration, bringing the initial bacterial concentration to approximately 1 × 10⁻⁶. 5CFU / mL. Centrifuge tubes were fixed in a constant temperature shaker at 37℃ and 100 rpm for 24 h. After incubation, 1.0 mL of the mixture was immediately serially diluted 10-fold. 0.1 mL of the appropriate dilution was spread onto nutrient agar plates and incubated at 37℃ for 24 h. The colony count was then calculated and compared with the blank control group without pellets to determine the antibacterial rate.
[0039] The deodorization performance was tested for ammonia and hydrogen sulfide. 50.0g of standard artificial fecal homogenate and 10.0mL of artificial urine were injected as odor sources into a sealed glass container with a total volume of 1.0L. A single test pellet was placed on a support inside the container, without direct contact with the liquid. A container with identical conditions but without the pellet was used as a blank control. After sealing, the container was placed in a constant temperature environment of 37℃ and continuously stirred at a low speed of 60rpm using a built-in micro magnetic stirrer. Using a calibrated portable gas detector, headspace gas was extracted through the sampling port at the beginning of the test (0h) and at 1h, 6h, and 24h after the pellet was added. The real-time concentration values (unit: ppm) of ammonia and hydrogen sulfide were recorded. The ammonia removal rate (%) after 24 hours was calculated using the following formula: [(ammonia concentration of the blank control group at 24h - ammonia concentration of the experimental group at 24h) / ammonia concentration of the blank control group at 24h] × 100%. The hydrogen sulfide removal rate (%) over 24 hours was calculated using the same formula.
[0040] Before the moisture absorption performance test, the pills were dried at 60℃ to constant weight, and their initial mass (M0) was recorded. Then, each pill was placed in a constant temperature and humidity chamber with an environment set at 37℃ and 90% relative humidity. After 6h, 24h, and 72h, the pills were quickly removed and weighed using an analytical balance, and their mass (M0) was recorded. t The moisture absorption rate (%) is calculated using the following formula: [(M t -M0) / M0]×100%. In the report, "72h moisture absorption rate / %" specifically refers to the value calculated using this formula at t=72h.
[0041] Mechanical integrity was assessed using an oscillation simulation test. Ten pills were placed in a 100mL capped transparent plastic bottle along with 50mL of simulated intestinal fluid (pH 8.0). The bottle was horizontally fixed on a shaker and continuously oscillated for 12 hours at a frequency of 60 Hz and an amplitude of 2cm. During oscillation, the number of pills with visible cracks or structural breakage was visually inspected and recorded every hour. At the end of 12 hours of oscillation, the total number of broken pills was counted. The "12-hour oscillation breakage rate (%)" was calculated using the following formula: (Total number of broken pills / Total number of tested pills × 10) × 100%.
[0042] The performance test data above are shown in Table 1.
[0043] Table 1 Performance Test Results As can be seen from the above, the technical solutions of the present invention represented by Examples 1-3, compared with Comparative Examples 1-3, systematically solve the key technical problems of existing stoma care products having single functions, short-lived effects, and inability to work synergistically.
[0044] Specifically, Comparative Example 1 uses a simple combination of ordinary zinc oxide and titanium dioxide. Its antibacterial performance (the antibacterial zone is only about 8 mm and the antibacterial rate is only about 30%) and deodorization performance (the ammonia removal rate is about 50% in 24 hours and it reaches saturation in 6 hours) are both seriously insufficient. It also has the lowest moisture absorption rate (22.4%) in 72 hours and the highest mechanical damage rate (40%). This verifies that the simple physical mixture or single component material in the existing technology cannot meet the long-lasting and multi-effect care needs of the ostomy bag.
[0045] Examples 1-3 achieved a leap in performance by introducing two core modified compounds: First, in terms of antibacterial properties, the inhibition zone diameter of Example 1 exceeded 19 mm and the antibacterial rate was as high as 99.98%, which is in stark contrast to Comparative Example 2 (which only used modified deodorant and did not use modified antibacterial agent, and its inhibition zone was only 9 mm with an antibacterial rate of about 85%). This proves that the mesoporous silica-supported silver-zinc oxide composite structure provides a strong and long-lasting antibacterial ability that ordinary zinc oxide cannot match through slow release and synergistic effect, fundamentally solving the risk of bacterial growth and infection.
[0046] Secondly, in terms of deodorization, Example 1 achieved an ammonia removal rate of over 96% in 24 hours, while the deodorization performance of Comparative Example 3 (using only modified antibacterial agent, without modified deodorizer) significantly decreased to about 58% after 6 hours. This confirms that the rare earth-doped zinc oxide / montmorillonite composite, with its enhanced adsorption and weak photocatalytic ability, has overcome the bottlenecks of easy saturation of traditional adsorption materials and failure of photocatalysts in the dark, and has achieved long-term deodorization in the closed environment of the ostomy bag.
[0047] Furthermore, the moisture absorption rates (28.6-40.5%) of Examples 1-3 were significantly higher than those of Comparative Examples 1 and 3, and the mechanical breakage rate after 12 hours was 0 or extremely low, indicating that the present invention, through optimized formulation and process, ensures the physical stability and reliability of the product while integrating multiple functions.
[0048] In summary, the data from Examples 1-3 fully demonstrate that the present invention, through the creative design and synergistic integration of two modified compounds, successfully integrates properties such as high-efficiency antibacterial properties, long-lasting chemical deodorization, rapid moisture absorption, and physical stability into one, thereby comprehensively solving the long-standing technical problems in a single sample, such as activated carbon sheets only adsorbing without antibacterial properties, short-lived effects of sprays, and the inability of various materials to work together to exert their functions in a sustained manner.
Claims
1. A method for preparing antibacterial, deodorizing, and moisture-absorbing pellets for fecal ostomy bags, characterized in that the steps include... include: S1. By weight, 15-25 parts of mesoporous silica-supported silver-zinc oxide composite antibacterial agent, 20-30 parts of rare earth-doped zinc oxide / montmorillonite composite photocatalytic deodorizer, 10-15 parts of rosin powder, 8-12 parts of magnesium stearate, 25-35 parts of activated carbon powder, and 10-15 parts of anhydrous calcium chloride powder are placed in the ball mill jar of a ball mill. Anhydrous ethanol is added, and argon gas is introduced. The mixture is ball-milled to obtain a ball mill slurry. The ball mill slurry is then transferred to a vacuum drying oven at 38-42℃ and dried to obtain a functional masterbatch. The functional masterbatch is transferred to a stirred pellet mill, and an anhydrous ethanol solution containing 8-12 parts of polyethylene glycol 6000 is added through a spray device under continuous stirring to obtain wet pellets. S2. Place the wet pellets into a drying oven and dry them first at 48-52℃, then at 88-92℃, and then at 98-102℃. After drying, cool them to 38-42℃ and age them. The preparation method of the mesoporous silica-supported silver-zinc oxide composite antibacterial agent includes: A1. Dissolving 0.4-0.6 parts by weight of hexadecyltrimethylammonium bromide in a mixture of 40-60 parts deionized water and 3-5 parts ammonia water, stirring, adding 1-1.5 parts of tetraethyl orthosilicate, and reacting at 38-42℃ to obtain a mixture; centrifuging the mixture to obtain a precipitate, washing the precipitate with deionized water until neutral, then replacing it with anhydrous ethanol, and then dispersing it in anhydrous ethanol to obtain a suspension; adding 0.03-0.0 parts by weight of hexadecyltrimethylammonium bromide in a mixture of 40-60 parts deionized water and 3-5 parts ammonia water, stirring, adding 1-1.5 parts of tetraethyl orthosilicate, and reacting at 38-42℃ to obtain a suspension ... adding 0.03-0.0 parts of tetraethyl orthosilicate in a mixture of 40-60 parts deionized water and 3-5 parts ammonia water, stirring, adding 1-1.5 parts of tetraethyl orthosilicate in a mixture of 40-60 parts deionized water and 3-5 parts ammonia water, and then dispersing it in anhydrous ethanol to obtain a suspension; adding 0.03-0. Dissolve 5 parts silver nitrate and 0.15-0.25 parts zinc nitrate in anhydrous ethanol, add 0.02-0.05 parts mercaptopropyltrimethoxysilane to obtain a mixed solution; add the mixed solution to the suspension and stir at 58-62℃ to obtain a reaction mixture; A2, centrifuge the reaction mixture to obtain a solid product, wash the solid product with ethanol, heat it to 395-405℃ in a tube furnace, and calcine it in a nitrogen / hydrogen atmosphere; after calcineation, cool it to room temperature in the furnace under continuous nitrogen / hydrogen atmosphere, and grind it; The preparation method of the rare earth-doped zinc oxide / montmorillonite composite photocatalytic deodorizer includes: B1, dissolving 0.5-0.7 parts by weight of zinc nitrate, 0.01-0.03 parts by weight of cerium nitrate and 0.005-0.015 parts by weight of lanthanum nitrate in deionized water to obtain solution A; dispersing 0.3-0.5 parts by weight of sodium-based montmorillonite in deionized water to obtain suspension B; adding solution A dropwise to suspension B while stirring, and simultaneously adding an aqueous solution containing 0.8-1.2 parts by weight of urea, adjusting the pH to 8.5-9.5, and reacting in a water bath at 84-86℃ to obtain a mixture; B2, centrifuging the mixture to obtain a solid product, washing the solid product, and drying it at 78-82℃ to obtain a dried powder; calcining the dried powder at 445-455℃ in an air atmosphere.
2. The preparation method of the antibacterial, deodorizing, and moisture-absorbing pellets for fecal ostomy bags according to claim 1, characterized in that, In step S1, the ball milling mixing time is 1.5-2 hours.
3. The preparation method of the antibacterial, deodorizing, and moisture-absorbing pellets for fecal ostomy bags according to claim 1, characterized in that, In step S2, the drying time at 48-52℃ is 1-2 hours.
4. The preparation method of the antibacterial, deodorizing, and moisture-absorbing pellets for fecal ostomy bags according to claim 1, characterized in that, In step A1, the reaction time at 38-42℃ is 2-4 hours.
5. The method for preparing the antibacterial, deodorizing, and moisture-absorbing pellets for fecal ostomy bags according to claim 1, characterized in that, In step A2, the calcination time in a nitrogen / hydrogen atmosphere is 3-6 hours.
6. The method for preparing the antibacterial, deodorizing, and moisture-absorbing pellets for fecal ostomy bags according to claim 1, characterized in that, In step B1, the reaction time in a water bath at 84-86℃ is 5-10 hours.
7. The preparation method of the antibacterial, deodorizing, and moisture-absorbing pellets for fecal ostomy bags according to claim 1, characterized in that, In step B2, the calcination time at 445-455℃ is 2-4 hours.
8. A type of antibacterial, deodorizing, and moisture-absorbing pellet for fecal ostomy bags, characterized in that, The antibacterial, deodorizing, and moisture-absorbing pellets for fecal diversion ostomy bags are prepared according to any one of claims 1-7.
Citation Information
Patent Citations
Efficient antibacterial deodorant
CN108408851A
Modified nano-zinc oxide compound for plastics and preparation method thereof
CN113549343A
